Tensile and High Cycle Fatigue Behavior of 316L and Fe-18Cr-22Mn-0.65N Stainless Steel at Stress Ratio of 0.1 at Room Temperature - Kumar C.S.; Singh V.; Mahobia G.S. (My University, 2025)
High cycle fatigue behavior of a high nitrogen-containing austenitic stainless steel, Fe-18Cr-22Mn-0.65N (HNS), with negligible nickel content (0.01%), is compared at the stress ratio of 0.1 with that of 316L. The endurance limits of the HNS and 316L were 475 MPa and 513 MPa, respectively. It is important to mention that the yield strength (279 MPa) and tensile strength (616 MPa) of the 316L were considerably lower than the respective 525 MPa and 914 MPa of the HNS, despite the endurance limit of the 316L being higher than that of HNS. On the other hand, the fatigue life of the 316L at higher stress levels (≥ 538 MPa) was lower than that of the HNS. The higher endurance limit of the 316L is associated with its marked strengthening, resulting from rapid cyclic work hardening during the initial cycles, as it was subjected to cyclic stresses above its yield strength. However, at higher stress levels (≥ 538 MPa), its fatigue life was lower than that of the HNS and there was an accumulation of large plastic strain resulting from the tensile mean stress (ratcheting), having little effect on the ratcheting of the HNS. © The Minerals, Metals & Materials Society 2024.